2019
DOI: 10.1155/2019/7810320
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Autophagic Flux Rescues Oxidative Damage and Mitochondrial Dysfunction to Protect against Intervertebral Disc Degeneration

Abstract: Oxidative stress-induced mitochondrial dysfunction and nucleus pulposus (NP) cell apoptosis play crucial roles in the development of intervertebral disc degeneration (IDD). Increasing studies have shown that interventions targeting impaired autophagic flux can maintain cellular homeostasis by relieving oxidative damage. Here, we investigated the effect of curcumin (CUR), a known autophagy activator, on IDD in vitro and in vivo. CUR suppressed tert-butyl hydroperoxide- (TBHP-) induced oxidative stress and mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 65 publications
2
107
0
Order By: Relevance
“…Percutaneous needle puncture has been shown to be an effective method of induction of disc degeneration [ 32 ]. After acclimatization, animals were anesthetized by inhalation of 2% fluothane in oxygen/nitrous oxide.…”
Section: Methodsmentioning
confidence: 99%
“…Percutaneous needle puncture has been shown to be an effective method of induction of disc degeneration [ 32 ]. After acclimatization, animals were anesthetized by inhalation of 2% fluothane in oxygen/nitrous oxide.…”
Section: Methodsmentioning
confidence: 99%
“…Some apoptosis, neural ingrowth, vascularization, and inflammation related terms and pathways were identified that were consistent with well-established molecular mechanisms of IDD (Kepler et al, 2013 ). The pathogenesis of IDD includes cellular oxidative stress, mitochondrial dysfunction and apoptosis (Kang et al, 2019 ). Endplate chondrocyte apoptosis is an important cause of the pathogenesis of cartilage endplate (CEP) degeneration, leading to the occurrence and development of intervertebral disc degeneration (IDD) (Wu et al, 2010 ; Li et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ROS-induced autophagy inhibition is also proved to cause oxidative stress in many cell types [ 81 83 ]. And by enhancing and restoring impaired autophagy during IDD, Kang et al affirmed that excessive ROS production could be suppressed to protect the mitochondrial hemostasis and ameliorate NP cell senescence [ 84 ].…”
Section: The Underlying Pathogenesis Of Cell Senescence In Iddmentioning
confidence: 99%